Identification of Finswimming Athletes' Talents Based on Criteria and Key Talents Using the Analytic Hierarchy Process (AHP) Approach: Systematic Literature Review - I Putu Bayu Ardhya Satrio; Dede Rohmat Nurjaya; Nina Sutresna (Journal of Physical Education Health and Sport, 2025)
Talent identification is a fundamental stage in developing competitive sports because it plays a role in determining the direction of long-term athlete development. In finswimming, the talent identification process requires a specific and multidimensional approach considering the different physical, technical, and physiological demands from conventional swimming. However, finswimming talent identification practices are still often carried out subjectively and have not been integrated into a systematic decision-making model. The goal of this study is to use the Analytic Hierarchy Process approach to perform a comprehensive literature evaluation and synthesis of scientific literature on finswimming athlete talent identification based on important criteria and talents, using a systematic literature review design guided by the PRISMA 2020 framework. The research process involved searching for publications published between 2015 and 2025 in the PubMed, ScienceDirect, and Google Scholar databases using the PRISMA 2020 criteria as a guide. Based on the selection process, four studies were determined to meet the inclusion criteria and a narrative and descriptive analysis was conducted. The synthesis results showed that physical and physiological characteristics, especially muscle strength and aerobic endurance, were the most important factors in determining finswimming skills, with technical and psychological factors coming in second. These findings show how the Analytic Hierarchy Process approach can help identify athletic talent in finswimming in an objective, methodical, and evidence-based manner.